Histological analysis of rat prostate under exogenous testosterone and low dose of oral selenium administration - Sergio Marcelino de Oliveira; Loiane dos Santos Silva; Rafaela Heloise Cardoso Ledesma; Rodolpho Gonçalves da Silva (Universidade do Estado de Mato Grosso, 2018)
Objective: to verify selenium effectiveness in maintenance of prostate tissue architecture. Method: experimental study using 20 adult 90-day-old male rats divided into the following groups: TG, 05 animals that received injectable testosterone; TSG, 05 animals that received injectable testosterone and weekly doses of selenium by gavage; CG1, 05 intact animals; CG2, 05 animals that received saline injection and saline by gavage. Results: characteristic architecture was found in tissue samples from animals of CG with cubic/prismatic secretory epithelium surrounded by fibro-muscular stroma. Animals of TG showed an increase in prostatic epithelium height, increase in the number of blood vessels in stroma and presence of proliferative lesions. Proliferative lesions were also found in tissue samples from animals of TSG, besides having improve in epithelial height, as seen in TG. Conclusion: it is concluded that selenium at this concentration has no effectiveness in modulating morphology of prostatic tissue of adult rats. RESUMO Objetivo: verificar a eficácia do selênio na manutenção da morfologia tecidual prostática. Métodos: estudo experimental, utilizando 20 ratos machos adultos, divididos em: TG, 05 animais que receberam testosterona injetável; TSG, 05 animais que receberam testosterona injetável e doses semanais de selênio por gavagem; CG1, 05 animais intactos; CG2, com 05 animais que receberam solução salina injetável e por gavagem. Resultados: uma arquitetura característica foi encontrada nas amostras teciduais dos animais do CG, com epitélio cúbico/prismático envolvido por estroma fibro-muscular. Nos animais do TG a próstata apresentou um epitélio com células mais altas, um aparente aumento no número de vasos sanguíneos no estroma, além da presença de lesões proliferativas. Também foram encontradas lesões proliferativas nas amostras teciduais dos animais do TSG, além de apresentarem maior altura do epitélio, como vistas no TG. Conclusão: conclui-se assim, que o Selênio, nesta concentração, parece não ser eficaz na proteção contra as modificações promovidas pela administração de T exógena em ratos adultos.